Critical Discourse Analysis: Theoritical Framework - Arini Hidayah, S.S, M.A; Widyashanti Kunthara Anindhita (Universitas Veteran Bangun Nusantara, 2022)
When we discuss critical discourse analysis, we are not only talking about assertions, but also about the structure and principles of discourse. Discourse principle and critical discourse analysis structures cannot be divorced from the connection or relationship between discourse and reality. The term